2020
DOI: 10.3390/plants9080936
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Leaf-Scale Wheat Powdery Mildew (Blumeria graminis f. sp. Tritici) Combining Hyperspectral Imaging and an SVM Classifier

Abstract: Powdery mildew (PM, Blumeria graminis f. sp. tritici) is a devastating disease for wheat growth and production. It is highly meaningful that the disease severities can be objectively and accurately identified by image visualization technology. In this study, an integral method was proposed based on a hyperspectral imaging dataset and machine learning algorithms. The disease severities of wheat leaves infected with PM were quantitatively identified based on hyperspectral images and image segmentation techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
2
31
0
4
Order By: Relevance
“…The visible light and near-infrared regions are the sensitive bands for spectral identification of different crop diseases and insect pests; furthermore, the spectral sensitivity bands of different crops and different diseases vary. The sensitive bands of wheat powdery mildew are located at 490–780 nm [ 57 ], and wheat powdery mildew monitoring is mainly based on the sensitive band [ 58 , 59 ], and different forms of disease VI can be established according to the reflection characteristics of the disease [ 7 , 8 , 9 ]. Disease emergence involves gradual development that alters internal tissue physiology and biochemistry, and, in turn, the external morphological structure, and then manifests externally as disease that can be detected by remote sensing.…”
Section: Discussionmentioning
confidence: 99%
“…The visible light and near-infrared regions are the sensitive bands for spectral identification of different crop diseases and insect pests; furthermore, the spectral sensitivity bands of different crops and different diseases vary. The sensitive bands of wheat powdery mildew are located at 490–780 nm [ 57 ], and wheat powdery mildew monitoring is mainly based on the sensitive band [ 58 , 59 ], and different forms of disease VI can be established according to the reflection characteristics of the disease [ 7 , 8 , 9 ]. Disease emergence involves gradual development that alters internal tissue physiology and biochemistry, and, in turn, the external morphological structure, and then manifests externally as disease that can be detected by remote sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, active investigations are carried out to develop methods and approaches for plant diseases remote diagnosis based on using hyperspectral visualization of plants reflectivity [7,8]. It was demonstrated that hyperspectral visualization methods can be used in detection and diagnosis of powdery mildew [9,10]. Various spectral indicators of plants diseased leafs have been established.…”
Section: Introductionmentioning
confidence: 99%
“…When a plant got infected by a specific disease, and then significant symptoms are shown on the leaves, which help in the identification and classification of that particular disease [7]. It is therefore essential to control and assess disease outspread [8]. A specific fungus or bacterium is frequently associated with the colour, scale, form, and margins of spots and blight (lesions).…”
Section: Introductionmentioning
confidence: 99%